Effect of a sulforaphane supplement on muscle soreness and damage induced by eccentric exercise in young adults: A pilot study - Shoichi Komine; Ikuru Miura; Nao Miyashita; Sechang Oh; Katsuyuki Tokinoya; Junichi Shoda; Hajime Ohmori (Physiological Reports, 2021)
Abstract Objective Excessive exercise increases the production of reactive oxygen species in skeletal muscles. Sulforaphane activates nuclear factor erythroid 2‐related factor 2 (Nrf2) and induces a protective effect against oxidative stress. In a recent report, sulforaphane intake suppressed exercise‐induced oxidative stress and muscle damage in mice. However, the effect of sulforaphane intake on delayed onset muscle soreness after eccentric exercise in humans is unknown. We evaluated the effect of sulforaphane supplement intake in humans regarding the delayed onset muscle soreness (DOMS) after eccentric exercise. Research Methods & Procedures To determine the duration of sulforaphane supplementation, continuous blood sampling was performed and NQO1 mRNA expression levels were analyzed. Sixteen young men were randomly divided into sulforaphane and control groups. The sulforaphane group received sulforaphane supplements. Each group performed six set of five eccentric exercise with the nondominant arm in elbow flexion with 70% maximum voluntary contraction. We assessed muscle soreness in the biceps using the visual analog scale, range of motion (ROM), muscle damage markers, and oxidative stress marker (malondialdehyde; MDA). Results Sulforaphane supplement intake for 2 weeks increased NQO1 mRNA expression in peripheral blood mononuclear cells (PBMCs). Muscle soreness on palpation and ROM were significantly lower 2 days after exercise in the sulforaphane group compared with the control group. Serum MDA showed significantly lower levels 2 days after exercise in the sulforaphane group compared with the control group. Conclusion Our findings suggest that sulforaphane intake from 2 weeks before to 4 days after the exercise increased NQO1, a target gene of Nrf2, and suppressed DOMS after 2 days of eccentric exercise.